ANALYSIS OF PRESUPPOSITION IN THE BROADCAST “KAMALA HARRIS DISCUSSES U.S RELATIONSHIP WITH ISRAEL” BY 60 MINUTES - Barus, Cicilia Clara Angel; Sijabat, Lulu Ribka Roito; Silalahi, Charles David Marudut (Cahaya Ilmu Bangsa Institute, 2025)
This research investigates the underlying assumptions evident in the “Kamala Harris Discusses U.S. Relationship with Israel” segment aired by 60 Minutes, delving into how these implicit beliefs inform the dialogue and affect audiences’ interpretations. Utilizing a descriptive qualitative methodology, the research pinpoints significant presuppositions, including the belief that Benjamin Netanyahu serves as the Prime Minister of Israel, the perception of the Biden-Harris administration’s capacity to sway international policies, the association of Iran with militant organizations like Hamas and Hezbollah, and the collective recognition of the Middle East as the central geopolitical framework. These presuppositions, derived from shared cultural, political, and social knowledge, facilitate effective communication by obviating the need for extensive explanations. The study underscores how these assumptions serve as crucial components in the communication process, shaping the audience’s grasp of the intricate matters pertaining to U.S.-Israel relations, military support, diplomacy, and regional stability in the Middle East. It stresses the important function of presuppositions in determining how delicate geopolitical subjects are articulated and comprehended by both speakers and receivers.